Inibição do receptor do fator ativador de plaquetas promove redução de déficits neurológicos e neuroproteção na isquemia e reperfusão cerebral murina - Eliana Cristina de Brito Toscano (2016)
Stroke is one of the most frequent causes of death and disability worldwide, and can cause a significant variety of clinical and socioeconomic burden. Different mechanisms are involved in the pathogenesis of stroke, for example, the inflammatory response after ischemia that contributes to the expansion of brain injury. Platelet activating factor receptor (PAFR) is constitutively expressed in the brain tissue and regulates several events, like inflammation and neuronal loss. Platelet activating factor (PAF) in high concentrations induces the exacerbated activation of PAF receptor that amplifies intracellular signaling cascades leading to blood-brain barrier damage, edema formation, recruitment of leukocytes and neuronal cell death. Using mice C57/BL6 (with 9 to 11 weeks old) wild type and lacking the PAF receptor (PAFR-/-), we investigate the relevance of this receptor during experimental transient global cerebral ischemia and reperfusion by bilateral common carotids occlusion (BCCAo). The mice were divided into sham and BCCAo groups. The sham being subjected to the same procedures that BCCAo, except carotid occlusion. PAFR deficiency improved neurological deficits associated with reduction of infarcted areas analized by triphenyltetrazolium chloride (TTC) and of the percentage of necrotic cavities areas and frequency of ischemic neurons by histometric analysis. In addition, PAFR deficiency prevents cleaved caspase-3 activation and vascular permeability increase and brain edema. Moreover, decreased brain levels of the cytokines tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1beta) and of the chemokine (C-X-C motif) ligand 1 (CXCL1) by ELISA were detected in PAFR-/- BCCAo animals compared with WT group. Taking together, our results suggest that PAFR activation is important for the development of global brain ischemia and reperfusion injury.